2018
DOI: 10.1590/0103-11042018s124
|View full text |Cite
|
Sign up to set email alerts
|

Programa Mais Médicos: mapeamento e análise da produção acadêmica no período 2013-2016 no Brasil

Abstract: RESUMO Com o propósito de fortalecer a Atenção Primária à Saúde (APS) no Brasil, o Programa Mais Médicos (PMM) foi criado em 2013, estruturado em três eixos estratégicos. Este estudo teve como objetivo analisar a produção científica no PMM, identificando a relevância dos estudos e seus efeitos para a política e elaborando uma síntese dos principais temas. A busca foi realizada no Portal Regional da Biblioteca Virtual em Saúde e na Plataforma de Conhecimento do PMM, sendo identificados 409 documentos. Após crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
19

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
0
5
0
19
Order By: Relevance
“…The PMM was established rather recently, in late 2013, but several positive effects were identified, especially in physician supply, with a reduction in the shortage and in inequalities in physician distribution 15,16,17,18 , since 78% of these professionals were allocated to priority municipalities (counties) 19 , a reduction in hospital admissions for PHC-sensitive conditions 20 , and an increase in investments in construction and renovation to improve the infrastructure in the UBS 21 .…”
Section: "Doctors For Brazil": Implications For the Training And Retementioning
confidence: 99%
“…The PMM was established rather recently, in late 2013, but several positive effects were identified, especially in physician supply, with a reduction in the shortage and in inequalities in physician distribution 15,16,17,18 , since 78% of these professionals were allocated to priority municipalities (counties) 19 , a reduction in hospital admissions for PHC-sensitive conditions 20 , and an increase in investments in construction and renovation to improve the infrastructure in the UBS 21 .…”
Section: "Doctors For Brazil": Implications For the Training And Retementioning
confidence: 99%
“…This represents a third of the total amount invested in the entire programme during one year. Other studies showed greater satisfaction with public care, less medical absenteeism at work, and improvements in the doctor-patient relationship 6111213…”
Section: The Resultsmentioning
confidence: 98%
“…Convém ressaltar que, no Brasil, a problemática do financiamento, da escassez e provisão de médicos é amplamente discutida na literatura científica 2,3,5 . Nesse contexto, a provisão de médicos para a APS encontra--se atualmente no centro de um crescente debate político, que inclui discussões sobre provimento emergencial de médicos para áreas desassistidas com mudanças na forma de alocação desses profissionais e formação de recursos humanos para o SUS que, junto ao financiamento, tem sido frequentemente apontada como uma estratégia essencial para a superação das iniquidades em saúde, das injustiças sociais e das desigualdades regionais no Brasil 5,38,39 .…”
Section: Discussionunclassified